Site-Specific Seismic Hazard Assessment and Ground Motion Selection for Nonlinear Time History Analysis - Safiraa, Faradina; Tajunissa, Yuyun; Darmawan, Muhammad Sigit; Wahyudi, Hendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This journal aims to study a comprehensive methodology involving Deterministic Seismic Hazard Analysis (DSHA), site-specific ground motion selection, spectral matching, and nonlinear dynamic analysis on Beribis Kendeng Waleri Fault. Seven strong ground motion records were selected from the PEER NGA-West2 database and spectrally matched to the target response spectrum derived from DSHA parameters. Local site effects were incorporated through a site response analysis using detailed subsurface soil data, which classified the site as Class E (very soft soil). The resulting surface-level acceleration time histories were used in nonlinear time history analysis to assess structural performance.